1957
DOI: 10.1161/01.cir.16.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Ebstein's Anomaly

Abstract: Ten cases of Ebstein's anomaly are presented and the literature is reviewed. Certain diagnostic features of the clinical profile, in particular the auscultatory findings, are emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1960
1960
1971
1971

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Three of our patients were asymptomatic at the time of examination. Similar observations were made by Marxsen (1886), Malan (1908), Heigel (1913), Wood (1956), and Mayer et al (1957). In our series all the patients except one developed fatigue and dyspnxa, which are the most common symptoms observed.…”
Section: Symptomatologysupporting
confidence: 91%
See 1 more Smart Citation
“…Three of our patients were asymptomatic at the time of examination. Similar observations were made by Marxsen (1886), Malan (1908), Heigel (1913), Wood (1956), and Mayer et al (1957). In our series all the patients except one developed fatigue and dyspnxa, which are the most common symptoms observed.…”
Section: Symptomatologysupporting
confidence: 91%
“…Kilby et al (1956) reported cyanosis in all their 9 cases and emphasized the diagnostic importance of this finding, although Wood (1956) believes that cyanosis is not an important feature of this disease. Mayer et al (1957) reported cyanosis in 6 of their 10 cases, while Kjellberg et al (1955) reported it in only one of their four. In our series 5 out of 11 cases had cyanosis: in two, cyanosis was present at birth, in one, it developed at the age of 47, and in one, it was present only on exposure to cold, while another developed it only after exertion.…”
Section: Symptomatologymentioning
confidence: 96%
“…Of these I0 were boys and 22 girls, a finding which, giving as it does a conspicuous female preponderance of more than 2: 1, is not in keeping with the majority of other recorded series (Baker, Brinton, and Channell, 1950;Mayer, Nadas, and Ongley, 1957;Vacca, Bussmann, and Mudd, I958;Schiebler et al, 1959;Genton and Blount, I967).…”
Section: Subjectsmentioning
confidence: 73%
“…Three of these were proven at autopsy, and in the fourth the clinical features (Mayer, Nadas, and Ongley 1957) as well as the catheter findings (Vacca, Bussmann, and Mudd, 1958), including intracardiac records, were pathognomonic. The summary of these is presented in Table VI.…”
mentioning
confidence: 89%